Pesan Cinta dan Kehangatan dalam Lirik Lagu Bertaut : Sebuah Kajian Hermeneutika - Bella Setyawati; Nina Queena Hadi Putri (Institut Nalanda, 2025)
Song lyrics as a form of literature have an important role in conveying emotional and social messages to listeners. The song “Bertaut” by Nadin Amizah is an example of a work that describes the emotional relationship between a child and his mother, which can be analyzed through a hermeneutic approach. This approach allows the interpretation of song lyrics not only based on literal meaning, but also through social, cultural, and individual experience perspectives. The purpose of this study is to uncover the meaning of love and warmth contained in the lyrics of the song “Bertaut” by applying hermeneutic theory, especially Hans-Georg Gadamer's fusion horizon, to understand the emotional dynamics in mother-daughter relationships. Through qualitative methods, this study found that the song is full of symbolism and metaphors, such as “linked heartbeats” and “friendless hedgehogs,” which depict strong inner bonds and relationships that transcend physical dimensions. The song also reflects how Nadin Amizah conveys gratitude and respect for her mother, and how listeners from different backgrounds can feel and interpret the meaning of the song according to their personal experiences. Thus, “Bertaut” is not only a personal expression for the composer, but also a universal work, allowing for deep interpretations from each listener.